Combined biologic removal of sulphate for tanning industrial wastewaters - Di Berardino, Santino (2010)
A biologic pretreatment technology of mixed tanneries wastewater, suitable for sulphate-rich industrial wastewaters, has been studied, in order to eliminate chemical precipitation and improve removal efficiency of the relevant pollutants. It couples an anaerobic reactor with an aerobic sulphide oxidant (ASO) step, where H2S2 is partially oxidized to elemental sulphur, and includes a recirculation system. The proposed solution provided Methanogenic Archae (MA) and Sulphate Reducing Bacteria (SRB) coexistence and controlled inhibition by partial oxidation of hydrogen sulphide.. The removal effiency of the anaerobic reactor was quite dependent on temperature and hydaulic retention time (HRT). COD removal varied between 32-68 % and sulphate removal (20-60%), referred to the mixture of the industrial effluent diluted with 50% of recirculation, at an Organic Load (OL) ranging from 0.5 to 1.5 kg CODM³ d⁻¹ and HRT from 1 to 5 days. The entire biologic pretreatment (AHF+ASO) resulted much more efficient and COD removal increased to 64-82% being less dependent on temperature variations. This process removed also a significant part (85%) of Chromium (Cr⁺³), by sorption into the biologic sludge. This two step biologic pretreatment, ensured better removal of relevant parameters than conventional chemical precipitation, avoided addition of chemical products, minimized excess sludge production, and also removed hydrogen sukphide and sulphate, resulting in a favorable alternative solution. The effluent from this stage was submitted to a sequencing batch nitrification/denitrification step, to improve the removal of the relevenat parameters. The average removal efficiency of entire process was appreciable and better than the conventional solution: COD = 88%, Sulphate = 68% and Nitrogen (kjeldahl) = 92%, chromium (Cr⁺³=96%). However, the presence of non degradable organic compounds delivered in the effluent from syntetic tanning, were hard to remove completely and did not allow fulfilling the severe standards for wastewater discharge in water course in terms of COD, Nitrogen (kjeldahl) and color. This requires and additional polishing step